2015
DOI: 10.1111/bjd.13437
|View full text |Cite
|
Sign up to set email alerts
|

Comparative efficacy of biological treatments for moderate-to-severe psoriasis: a network meta-analysis adjusting for cross-trial differences in reference arm response

Abstract: A model adjusted for reference arm response rates was found to fit clinical trial data significantly better than unadjusted models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
52
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 42 publications
5
52
0
3
Order By: Relevance
“…Six NMAs (Bansback et al., 2009, Gomez-Garcia et al., 2017, Lin et al., 2012, Reich et al., 2012, Signorovitch et al., 2015, Woolacott et al., 2006) have been published examining the relative efficacy of biologics for psoriasis. Treatment tolerability is an important consideration for patients, with such concerns directly influencing whether patients adhere to treatment after initiation (Thorneloe et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Six NMAs (Bansback et al., 2009, Gomez-Garcia et al., 2017, Lin et al., 2012, Reich et al., 2012, Signorovitch et al., 2015, Woolacott et al., 2006) have been published examining the relative efficacy of biologics for psoriasis. Treatment tolerability is an important consideration for patients, with such concerns directly influencing whether patients adhere to treatment after initiation (Thorneloe et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Persistence measured under optimal (standardized) conditions in prescreened, highly motivated patient populations, using tight protocols and independent investigators during clinical trials does not necessarily coincide with the drug survival of therapies prescribed in the real-world settings (10,11). There are studies on the short-term persistence of biological therapies used in psoriasis; however, very limited comparative evidence is available on the long-term persistence of biological therapies used in the real-world settings (12). The objectives of this study were to analyze the characteristics of all psoriasis patients treated with any of the biological therapies currently marketed in Hungary (adalimumab, etanercept, infliximab, ustekinumab), to compare long-term drug survival of such therapies in the real-world settings and also to assess the impact of additional factors, like patient age, gender, biological therapynaïve status or the use of methotrexate (MTX) on drug survival.…”
Section: Introductionmentioning
confidence: 99%
“…Lists of excluded trials and reasons for exclusion were also reviewed and relevant trials identified. To supplement this review, the results of a recently published systematic review and NMA, 103 which adjusted for cross-trial differences in the comparative efficacy of biological treatments for moderate to severe psoriasis in adults, were also examined to cross-check that the majority of relevant studies had been identified in the…”
Section: Framework Of Analysis For Informing the Relative Efficacy Ofmentioning
confidence: 99%
“…placebo response) were explored. 103 These models impose a common interaction effect between baseline risk and relative effectiveness that accounts for variation in reference arm response across trials. NMA meta-regression models that explore variability caused by age effects were also implemented.…”
Section: Evidence Synthesis To Inform the Relative Efficacy Of The Inmentioning
confidence: 99%
See 1 more Smart Citation